Roland Hall interviewed by Bruce Simpson and Bill Gammage in the Drovers oral history project - Hall, Roland, 1932-; Simpson, Bruce (Bruce Forbes), 1923-2019; Gammage, Bill, 1942- (2005)
Roland Hall talks about his father's drilling background; the acquisition of Ooratippra Station; his childhood in the Alice Springs area; characters in Alice Springs during his childhood, Bob Buck, Drummond Hay; working on his father's cattle property until age 21; the sale of the property (1966); working as truck driver, mechanic and driller; the early drilling plant, the drilling process, the use diesel and steam; water divining; his knowledge of landscape when finding water; the current usage of percussion and modern drills; payment rates; stock water supplies; water storage; drought; the Indigenous population on Ooratippra; traditional land; his marriage (1961) and return to Ooratippra Station; the introduction of drilling licenses in S. Aust, W.A. and N.T; drilling techniques, bores, equipment; modern pumping methods; the use of windmills and engines; water quality; drilling locations over his career; bore rehabilitation; camping out at bore sites, work and living conditions; his retirement from drilling work; care-taking on stations, bore maintenance; the modern Alice Springs; Alice Springs' declining water supply, pollution of town basin; recharging of artesian basins; future water sources; underground water, artesian supplies; drilling bores for Aboriginal Communities; gold prospectors, Lasseter's Reef; Ben Nicker; his friendship with drilling offsider, Banjo.
Recorded on April 04, 2005 at Alice Springs, N.T.
Also available online
Timed summary and uncorrected transcript (typescript, 58 leaves) available.
Keywords: Hall, Roland, -- 1932- -- Interviews; Boring -- Australia; Water-supply -- Australia; Water-supply engineering -- Australia